Alterations of Regional Homogeneity in Parkinson’s Disease Patients With Freezing of Gait: A Resting-State fMRI Study - Liu, Yanjun; Li, Mengyan; Chen, Haobo; Wei, Xinhua; Hu, Guihe; Yu, Shaode; Ruan, Xiuhang; Zhou, Jin; Pan, Xiaoping; Li, Ze; Luo, Zhenhang; Xie, Yaoqin (Frontiers in Aging Neuroscience, 2019)
Objective: The purpose of this study is to investigate the regional homogeneity (ReHo) of spontaneous brain activities in Parkinson’s disease (PD) patients with freeze of gait (FOG) and investigate the neural correlation of movement function by resting-state functional magnetic resonance imaging (RS-fMRI). Methods: A total of 35 normal controls (NC), 33 PD patients with FOG (FOG+) and 35 PD patients without FOG (FOG-) were enrolled. ReHo was applied to evaluate regional synchronization of spontaneous brain activities. Analysis of covariance (ANCOVA) was performed on ReHo maps of the three groups, followed by post-hoc two-sample t-tests between every two groups. Moreover, ReHo signals of FOG+ and FOG- were extracted across the whole brain and correlated with movement scores (FOG Questionnaire, FOGQ; Gait and Falls Questionnaire, GFQ). Results: Significant ReHo differences were observed in the left cerebrum. Compared to NC, ReHo of PD subjects was increased in the left angular gyrus (AG), while decreased in the left rolandic operculum/postcentral gyrus (Rol/PostC), left inferior opercular-frontal cortex, left middle occipital gyrus and supramarginal gyrus (SMG). Compared to that of FOG-, ReHo of FOG+ was increased in the left caudate and decreased in the left Rol/PostC. Within the significant regions, ReHo of FOG+ was negatively correlated with FOGQ in left SMG/PostC (r = -0.39, p < 0.05). Negative correlations were also observed between ReHo and GFQ/FOGQ (r = -0.36/-0.38, p < 0.05) in left superior temporal gyrus of whole brain based on AAL templates. Conclusion: The ReHo analysis suggested that the regional signal synchronization of brain activities of the FOG+ was the most active in the left caudate and the most hypoactive in the left Rol/PostC. It also indicated that ReHo in the left caudate and left Rol/PostC was critical in identifying the three groups. The correlation between ReHo and movement scores (GFQ/FOGQ) in left superior temporal gyrus was potential to differentiate FOG+ from FOG-. This study provided new insight into the understanding of PD with and without FOG.